Efficacy of Low-Pressure Inflation of Oversized Drug-Coated Balloon for Coronary Artery Disease - Katsumi Ueno; Norihiko Morita; Yoshinobu Kojima; Hiroki Kondo; Hiroshi Takahashi; Shingo Minatoguchi; Sho Higuchi; Yu Ando; Masayasu Esaki (Journal of Interventional Cardiology)
Objectives. This study sought to assess the efficacy of oversized drug-coated balloon (DCB) inflation at low pressure for the prevention of acute dissections and late restenosis. Background. The major limitation of DCB coronary angioplasty is the occurrence of severe dissection after inflation of DCB. Methods. Between 2014 and 2018, 273 consecutive patients were retrospectively studied. 191 lesions (154 patients) treated by oversized DCB inflation at low pressure (<4 atm, 2.4 ± 1.2 atm, DCB/artery ratio 1.14 ± 0.22; LP group) were compared with 135 lesions (119 patients) treated by the standard DCB technique (7.1 ± 2.2 atm, DCB/artery ratio 1.03 ± 0.16; SP group). Results. Although the lesions in the LP group were more complex than those in the SP group (smaller reference diameter (2.38 mm vs. 2.57 mm, P=0.011), longer lesions (11.7 mm vs. 10.5 mm, P=0.10), and more frequent use of rotational atherectomy (45.0% vs. 28.1%, P=0.003), there was no significant difference in the NHLBI type of dissections between the two groups (11.5%, 12.0%, 5.2% vs. 12.6%, 12.6%, 2.2% in type A, B, and C, P=0.61), and no bailout stenting was required. In 125 well-matched lesion pairs after propensity score analysis, the cumulative incidence of target lesion revascularization at 3 years was 4.5% vs. 7.0%, respectively (P=0.60). Late lumen loss (−0.00 mm vs. −0.01 mm, P=0.94) and restenosis rates (7.4% vs. 7.1%, P=1.0) were similar in both of the groups. Conclusion. The application of oversized DCB at low pressure is effective and feasible for preventing late restenosis comparative to the standard technique of DCB.